Training on Processing Natural Resources into Processed Food and Health Products for Mothers in Tondongggeu Village, Nambo District, Kendari City - Ambardini, Sri; Ahmad, Sitti Wirdhana; Muhsin, Muhsin; Karya, Adi; Syah, Muhamad Azwar; Adi Parman Rudia, La Ode; Yanti, Nur Arfa (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2024)
This community service activity is a training activity on the manufacture of health and food products that have the opportunity to improve the community's economy as well as providing education on the use of moringa leaves as face masks and papaya fruit as an analog tomato sauce to mothers in Tondonggeu Village, Nambo District, Kendari City. Tomato sauce is generally made from tomato raw materials, but it can also be made from other ingredients so it is called an analog tomato sauce. Tomato sauce is generally made from tomato raw materials, but it can also be made from other ingredients so it is called an analog tomato sauce. Papaya as a substitute for tomatoes in making analog tomato sauce can be done because papaya has characteristics like tomatoes, namely color, organic acid content, and viscosity, even papaya has a higher vitamin C level than tomatoes. Moringa leaves contain many vitamins, including vitamin A, vitamin C, amino acids and antioxidants such as flavonoids, quercetin and zeatin which function to maintain dry skin hydration and prevent the appearance of wrinkles, because it helps fight free radicals, so it is very good to be used as a cosmetic ingredient in the form of a face mask. Participants in this training involved residents of Tondonggeu village, Thematic KKN students and a team of accompanying lecturers from the Biotechnology and Biology study program of FMIPA Halu Oleo University. The training methods used are lectures, demonstrations and discussions. The lecture method was carried out with the aim of providing information and knowledge about moringa masks and analog ketchup. The demonstration aims to provide skills to mothers through the practice of directly processing moringa leaves into masks and papaya fruits into analog tomato sauce while the discussion is intended to show the activeness and understanding of the community during the training process. The results of the training on making masks and analog tomato sauce carried out by mothers are in the good category with an average success of 85%, their response to the implementation of the training is very good as seen from the enthusiasm of the residents to participate in the activity from the beginning to the end. This training activity can increase knowledge and improve mothers' skills in producing moringa masks and papaya analogue tomato sauce.